Pengaruh Kecerdasan Emosional, Kompetensi Dan Motivasi Berprestasi Terhadap Kinerja Karyawan pada RS. Tk III. Dr. Reksodiwiryo Padang (Studi Kasus Pada Staf Non Medis) - azizi, putri; Mulyadi, Olandari; Afuan, Muhammad (Riset Sinergi Indonesia, 2022)
The purpose of this study was to investigate the effect of emotional intelligence, competence and achievement motivation on employee performance in the Hospital Level III. Dr. Reksodiwiryo Padang (Case Study: Non Medical Staff). The study consists of three independent variables of emotional intelligence, competence, achievement motivation and the dependent variable employee performance. The analytical method used is the multiple regression analysis and hypothesis testing. Methods of data collection in this study is the use of questionnaires filled out by respondents are Hospital Level III. Dr. Reksodiwiryo Padang (Case Study: Non Medical Staff). The results showed that: 1) Emotional Intelligence with the result t is greater than t table (3,661 >1,660) or the level is significantly smaller than alpha (0.000<0.05), the Emotional Intelligence positive and significant effect on employee performance. 2). Competence with the result t is greater than t table (4,596>1,660) or the level is significantly smaller than alpha (0.000<0.05) the competencies and significant positive effect on employee performance. 3). Achievement Motivation result t is greater than t table (9,810 >1,660) or the level is significantly smaller than alpha (0,000>0,05), Achievement Motivation positive and significant effect on employee performance. 4). Emotional Intelligence, Competencies and Achievement Motivation jointly significant effect on employee performance, which results t is greater than t table (5.062>1,660) or the level is significantly smaller than alpha (0,000<0.05).